The Effectiveness of a Peer Coaching Education on Control and Management of Type 2 Diabetes in Women: A Protocol for a Randomized Controlled Trial - Maryam Aalaa; Mahnaz Sanjari; Hamid Reza Aghaei Meybodi; Mohammad Reza Amini; Mostafa Qorbani; Hossien Adibi; Neda Mehrdad (Shiraz University of Medical Sciences, 2017)
Background: Diabetes Education by Peer Coaching is a strategy which helps the patients with diabetes in the field of behavioral and emotional problems. However, the results of studies in this field in other countries could not be generalized in our context. So, the current study aimed to examine the effectiveness of Diabetes Education by Peer Coaching on Diabetes Management. Methods: Outcome variables for patients and peer coaches are measured at baseline and in3,6 and 12 months. The primary outcome consisted of Fasting Blood Sugar (FBS) and HbA1c. Secondary outcomes included Blood Pressure (BP), Body Mass Index (BMI,) Waist-Hip Ratio (WHR), Lipid Profile, diabetes self-care activities, diabetes-related quality of life, depression, and Social Capital levels.Initial analyses compared the frequency of baseline levels of outcome and other variables using a simple Chi-square test, t-test and the Mann-Whitney- U test. Sequential measurements in each group were evaluated by two-way analysis of variance. If significant differences in baseline characteristics were found, analyses were repeated adjusting for these differences using ANOVA and logistic regression for multivariate analyses. Additional analyses were conducted to look for the evidence of effect modification by pre-specified subgroups. Conclusion: The fact is that self-control and self-efficacy in diabetes management and treatment of diabetes could be important components. It seems that this research in this special setting with cultural differences would provide more evidence about peer-coaching model. It seems that if the peer-coaching model improves learning situations between patients with diabetes by offering one-on-one Diabetes Self Management Education, it could be an interactive approach to diabetic education